2021
DOI: 10.3389/fimmu.2021.616074
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Prolongs Mouse Heart Allograft Survival by Activating T Cell Apoptosis via the Mitochondrial Pathway

Abstract: Berberine, which is a traditional Chinese medicine can inhibit tumorigenesis by inducing tumor cell apoptosis. However, the immunoregulatory of effects berberine on T cells remains poorly understood. Here, we first examined whether berberine can prolong allograft survival by regulating the recruitment and function of T cells. Using a major histocompatibility complex complete mismatch mouse heterotopic cardiac transplantation model, we found that the administration of moderate doses (5 mg/kg) of berberine signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Anti-PD-1 mAb combined with apigenin could effectively enhance the cytotoxic effect of CD8+ T cells with an increased level of TNF-α, IFN-γ, and granzyme B in the Lewis lung carcinoma model that did not respond to treatment with anti-PD-1 mAb alone [87]. Berberine (BBR), an isoquinoline alkaloid derived from Coptidis chinensis Franch and Phellodendron chinense Schneid, exerts an anti-tumor effect on many cell types (e.g., non-small-cell lung cancer (NSCLC) cells and breast cancer cells), of which the anti-tumor effect is abolished in T-cell-deficient mice models, suggesting that immunomodulatory effects of BBR are associated with T cell action [88]. Liu et al found that BBR could promote PD-L1 degradation through the ubiquitin/proteasome-dependent pathway and inhibit the PD-1/PD-L1 axis through deubiquitination activity, resulting in effective down-regulation of PD-L1 expression and counteraction of IFN-γ-induced PD-L1 upregulation in vitro and in vivo [89].…”
Section: Natural Compounds Promoted the Killing Of Cancer Cellsmentioning
confidence: 99%
“…Anti-PD-1 mAb combined with apigenin could effectively enhance the cytotoxic effect of CD8+ T cells with an increased level of TNF-α, IFN-γ, and granzyme B in the Lewis lung carcinoma model that did not respond to treatment with anti-PD-1 mAb alone [87]. Berberine (BBR), an isoquinoline alkaloid derived from Coptidis chinensis Franch and Phellodendron chinense Schneid, exerts an anti-tumor effect on many cell types (e.g., non-small-cell lung cancer (NSCLC) cells and breast cancer cells), of which the anti-tumor effect is abolished in T-cell-deficient mice models, suggesting that immunomodulatory effects of BBR are associated with T cell action [88]. Liu et al found that BBR could promote PD-L1 degradation through the ubiquitin/proteasome-dependent pathway and inhibit the PD-1/PD-L1 axis through deubiquitination activity, resulting in effective down-regulation of PD-L1 expression and counteraction of IFN-γ-induced PD-L1 upregulation in vitro and in vivo [89].…”
Section: Natural Compounds Promoted the Killing Of Cancer Cellsmentioning
confidence: 99%
“…Berberine (BBR) is a quaternary ammonium alkaloid extracted from Rhizoma coptidis with multiple biochemical and pharmacological activities, including anti‐apoptosis and cardioprotective effects. 7 , 8 , 9 , 10 Notably, the effects of BBR on MIRI have attracted the attention of researchers. For instance, Zhu et al revealed that BBR could protect against MIRI via promoting cardiomyocytes proliferation and suppressing the apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) is a quaternary ammonium alkaloid extracted from Rhizoma coptidis with multiple biochemical and pharmacological activities, including anti‐apoptosis and cardioprotective effects 7–10 . Notably, the effects of BBR on MIRI have attracted the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%